News-driven business cycles in SVARs - Patrick Bunk (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Recent studies proposed news about future technology growth as the main driver of macroeconomic fluctuations. The identification of these news through stock prices in SVARs has been criticized in the past. Therefore, I propose a series of experiments to test that hypothesis by examining its implications. If business cycles are mainly driven by news then these shocks should be captured by other time series as well. I find that news shocks identified through S&P 500 prices exhibit the same dynamics as news identified through a broader stock price index, patent applications, the relative price of investment or shocks to the real interest rate. The common theme among these identifications is a technological change in productivity that demands time to build, economic activity and natural resources to come into effect.
Keywords: E30; E32; 330; business cycles; news shocks; technological progress; Konjunktur; Wirtschaftsinformation; Technischer Fortschritt; Schock; Börsenkurs; VAR-Modell; Theorie; Schätzung; USA